155 The role of palliative medicine in end stage duchenne muscular dystrophy. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Mburu, Brian; Willis, Derek
Abstract : Background: Duchenne Muscular Dystrophy (DMD) is a progressive muscle wasting disease. It is the most common type of muscular dystrophy in the UK. Those affected usually die in their late 20 s or early 30 s due to cardiac or respiratory problems. As the disease progresses they may need management of symptoms arising from complications of late disease, such as pain. This poster looks into the joint services provided by the community palliative team at Shrewsbury and Telford Severn hospice and the Oswestry neuromuscular clinic caring for five patients with advanced Duchenne muscular dystrophy. Methods: The notes from the clinic consultations of the five patients involved were perused and the consultations noted, along with the proposed management plan. Subsequent clinic follow ups were looked into to review response to the management plan and note any amendments to treatment that were made. Results: The five patients presented with pain as their main symptom. Different choices of analgesia were tried with different responses. All patients reported improvement in their symptoms after starting analgesia with some requiring a combination of analgesics. In addition to this, some of the patients required input from other services regarding other aspects of patient care, such as the respiratory team for sleep studies and assessment for ventilatory support, or access to the hospice for various social events in a safe and welcoming environment. Conclusion: As there are no guidelines for management of DMD, management may involve trials of different analgesia for pain management in addition to involvement of a multi-disciplinary team to address other care issues. As palliative medicine involves symptomatic treatment of patients with advanced and terminal disease and holistic care, there is a role for palliative medicine in management of patients with end stage Duchenne muscular dystrophy.